Discovering Indonesian Islam Through Fatâwâ - Ahmad Fathan Aniq (Universitas Islam Negeri Mataram, 2008)
In the field of Indonesian-Islam studies, Hooker’s ‘Indonesian Islam’ is a welcome contribution to the scholarship. Unlike other Western scholars who study Indonesian Islam through anthropology, Hooker through his publication tries to show us that Islam in contemporary Indonesia can be known from fatâwâ (pl. fatwa) that have been responding matters of Indonesian Muslim society, have colored them and have been followed by them. For this reason, Hooker chooses four main Indonesian fatwa-issuing institutions which have been responding to challenges of modernity. They are Persatuan Islam (Persis), Muhammadiyah, Nahdlatul Ulama (NU) and Majelis Ulama Indonesia (MUI) and further, they are called “sources” or sources of fatâwâ. As a focus of the study, Hooker takes the fatâwâ from 1920s to the 1990s, from the period of colonialism to independence, which encompass the vast political, social and legal changes of this period.